2021
DOI: 10.1093/advances/nmaa113
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Nuts or Nut Products Does Not Lead to Weight Gain, Independent of Dietary Substitution Instructions: A Systematic Review and Meta-Analysis of Randomized Trials

Abstract: Several clinical interventions report that consuming nuts will not cause weight gain. However, it is unclear if the type of instructions provided for how to incorporate nuts into the diet impacts weight outcomes. We performed a systematic review and meta-analysis of published nut-feeding trials with and without dietary substitution instructions to determine if there are changes in body weight (BW) or composition. PubMed and Web of Science were searched through 31 December 2019 for clinical trials involving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 109 publications
(116 reference statements)
3
52
1
Order By: Relevance
“…While this heterogeneity could not be adequately assessed categorically for the cohorts as there were too few cohort studies, subgroup analyses and meta-regression of the trials identified potential sources of heterogeneity. For the trials, similar to the previous publications, 36,37 energy balance was identified as a potential source of heterogeneity.…”
Section: Discussionmentioning
confidence: 83%
“…While this heterogeneity could not be adequately assessed categorically for the cohorts as there were too few cohort studies, subgroup analyses and meta-regression of the trials identified potential sources of heterogeneity. For the trials, similar to the previous publications, 36,37 energy balance was identified as a potential source of heterogeneity.…”
Section: Discussionmentioning
confidence: 83%
“…A meta-analysis indicates that consumption of dairy products may be associated with a decreased risk of obesity [ 30 ]. Studies also show that incorporating nuts into diets does not lead to weight gain and may aid weight maintenance [ 31 , 32 ]. In contrast, epidemiological evidence has demonstrated that the presence of processed foods, which are typically high in salt, fat, and sugar, lead to a high prevalence of overweight/obesity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, given that nuts have low carbohydrates and are rich in polyunsaturated fatty acids (PUFAs) and fibers, the intake of nuts could raise the subsequent perception of satiety [ 4 , 8 ] and, as a consequence, reduce the total amount of energy intake. Indeed, a recent systematic review of randomized controlled trials (RCTs) noted that the intake of nuts or nut products did not lead to weight gain [ 9 ]. Although RCTs provide well-controlled higher-quality data, observational studies provide real-world and more generalizable evidence on the risks and benefits of diet-related exposures [ 10 ], such as nut consumption.…”
Section: Introductionmentioning
confidence: 99%